EFEKTIFITAS PENGELOLAAN PERTAMBANGAN TERHADAP SUMBER DAYA ALAM DI INDONESIA (Faculty of Law, University of Palembang, 2023)
The effectiveness of mining management of natural resources has a major influence on the environment and society. Good mining management will certainly prevent environmental damage due to the activities of mining companies in an area. Apart from that, the existence of good mining management can certainly provide increased social welfare for the local community by creating employment opportunities for the community. Of course, this must also be supported by the government's role in issuing policies in the form of balanced laws and regulations for the parties. The legal regulations issued by the government are expected to be able to provide solutions for the parties to be able to fight for the interests of each party (mining companies and the community) in order to realize more development in mining management in the future.